Tunable Contact Angle Hysteresis for Component Placement on Stretchable Superhydrophobic Surfaces. Issue 12 (3rd April 2018) - Balan, Catalin Mihai; Vlandas, Alexis; Senez, Vincent
Abstract: One of the promising strategies to achieve high performance flexible electronics is to integrate high performance components (micro‐electro‐mechanical systems, integrated circuit, etc.) on a flexible substrate. The heterointegration of fragile high performance components, for example, thinned down 100 GHz silicon technology, necessitate however methodologies to place these components on the substrate while exerting as little force as possible to prevent any damage from occurring. In this work, a novel approach is presented for component positioning by capillary assembly on a smart flexible substrate composed of two layers of polymers. It is shown how the wettability of the surface can be engineered by combining stretching induced deformation of the top layer with plasma treatment. Using magnetically actuated ferrofluid droplets which carry the silicon chip shows how it can be aligned and deposited at predetermined sites on these substrates. It is demonstrated that unlike standard capillary alignment which relies on a hydrophobic/hydrophilic contrast, in this case deposition is controlled by surface adhesion contrast between the site and the rest of the substrate. Furthermore, it is explained how deposition sites can be selectively activated through localized stretching thus producing generic smart substrates on which precise depositions sites can be activated according to the needs of the end user. Abstract : A novel approach for component positioning on a smart flexible substrate is successfully demonstrated. The bilayer substrates surfaces are engineered by combining stretching induced deformation followed by plasma treatment to control their dynamic wettability while keeping them superhydrophobic. It is shown how small silicon parts can be assembled at predetermined deposition sites on these substrates using magnetically actuated droplets.